2017
DOI: 10.1186/s41100-017-0112-0
|View full text |Cite
|
Sign up to set email alerts
|

A new polymethylmetacrylate membrane improves the membrane adhesion of blood components and clinical efficacy

Abstract: Background: Hemodialysis with polymethylmetacrylate (PMMA) membrane dialyzers allows unique protein adsorption. New PMMA dialyzers should demonstrate equivalent protein adsorption, but improved hemocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The newly developed PMMA membrane, NF, was reported to suppress platelet activation during dialysis by reforming the membrane surface and have the same adsorption property as the conventional PMMA membrane, BG [12,13]. Activated platelets are related directly or indirectly to the development of the inflammatory response: activated platelets release pro-inflammatory substances [23] and induce the production of pro-inflammatory substances from white blood cells by activation that is induced by forming a complex [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The newly developed PMMA membrane, NF, was reported to suppress platelet activation during dialysis by reforming the membrane surface and have the same adsorption property as the conventional PMMA membrane, BG [12,13]. Activated platelets are related directly or indirectly to the development of the inflammatory response: activated platelets release pro-inflammatory substances [23] and induce the production of pro-inflammatory substances from white blood cells by activation that is induced by forming a complex [24].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings described above, we suspect that PS membranes that have inferior biocompatibility may have been included in the PS group in this study. It has been reported that NF has a lower platelet activation property compared with conventional PMMA membranes [12,13] Results were expressed as the mean ± standard deviation inflammatory cytokines, and the released cytokines directly and indirectly activate other platelets and lead to a reduction in the platelet count. NF can remove inflammatory cytokines by adsorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrafiltration rate during each dialysis session was no more than 8.9 mL/h/kg. The total amounts of albumin in the effluent dialysate by using NF-1.6H® (4-h duration, blood flow 270 mL/min, dialysate flow 500 mL/min) was reported to be about 1.8 g/HD session [9]. She discontinued HD after 11 sessions, at which time her serum creatinine level was decreased to around the baseline value 28 days after discontinuation of HD.…”
Section: Casementioning
confidence: 99%